The eukaryotic genome, its reads, and the unfinished assembly. Issue 14 (30th May 2013) - Muñoz, José Fernando; Gallo, Juan Esteban; Misas, Elizabeth; McEwen, Juan Guillermo; Clay, Oliver Keatinge
Abstract : In recent years, readily affordable short read sequences provided by next‐generation sequencing (NGS) have become longer and more accurate. This has led to a jump in interest in the utility of NGS‐only approaches for exploring eukaryotic genomes. The concept of a static, 'finished' genome assembly, which still appears to be a faraway goal for many eukaryotes, is yielding to new paradigms. We here motivate an object‐view concept where the raw reads are the main, fixed object, and assemblies with their annotations take a role of dynamically changing and modifiable views of that object. Abstract : Length, quality and production of affordable short NGS read sequences have significantly improved. A truly finished eukaryotic genome assembly is a rare achievement. Static genome assemblies are not needed for some biological analyses. We propose an alternative role for assemblies as dynamic views of the primary reads.